1992
DOI: 10.1128/jvi.66.8.5157-5160.1992
|View full text |Cite
|
Sign up to set email alerts
|

Genetic assay for multimerization of retroviral gag polyproteins

Abstract: We have established a genetic assay for the multimerization of retroviral gag polyproteins. This assay is based on the GAL4 two-hybrid system for studying protein-protein interactions (S. Fields and 0. Song, Nature (London) 340:245-246, 1989). In our initial experiments, we generated Saccharomyces cerevisiae plasmids that separately express the GAL4 DNA-binding and GAL4 activation domains fused to the human immunodeficiency virus type 1 (HIV-1) gag polyprotein, Pr55w*. The coexpression of these two hybrid prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…Self-interactions of viral nucleocapsid protein (N-N interaction) or multimerization, have been well documented and suggested to be critical to the formation of viral nucleocapsid core, an important composition in the viral particle assembly and maturation in a variety of viral systems [11][12][13][14][15][16][17][18]. The multimerization of nucleocapsid proteins of coronaviruses is possibly a functional form of the protein, which may be involved in the virion assembly by stabilizing the helical structure of the N protein [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-interactions of viral nucleocapsid protein (N-N interaction) or multimerization, have been well documented and suggested to be critical to the formation of viral nucleocapsid core, an important composition in the viral particle assembly and maturation in a variety of viral systems [11][12][13][14][15][16][17][18]. The multimerization of nucleocapsid proteins of coronaviruses is possibly a functional form of the protein, which may be involved in the virion assembly by stabilizing the helical structure of the N protein [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, no similar functional roles of SARS-CoV have been reported so far in the literature except that SARS-CoV N may selectively activate AP-1 pathway [10]. Furthermore, while it is of note that self-interaction of nucleocapsid proteins (N-N interaction) and N protein interactions with other viral proteins have been reported to be one of the crucial steps in the formation and assembly of viral particles [11][12][13][14][15][16][17][18]. Such proteinprotein interactions, especially N-N self-interaction in coronaviruses, are poorly documented.…”
mentioning
confidence: 95%
“…As an additional route to identifying VLP structural elements, we used a yeast two-hybrid system in an attempt to detect subunit interactions. A similar strategy has been employed by Luban et al (1992) and Li et al (1996) with human immunodeficiency virus (HIV) gag and Moloney murine leukaemia virus (MoMLV) env proteins, respectively. Various fragments ( Fig.…”
Section: Determinants Of Protein-protein Interactionmentioning
confidence: 99%
“…3) giving high levels of b -galactosidase activity. As with HIV gag proteins (Luban et al, 1992), it seems therefore that the two-hybrid system is capable of detecting subunit interactions. Deletion of 30 amino acids from the N-terminus of the # 1996 Blackwell Science Ltd, Molecular Microbiology, 22, 667-679…”
Section: Determinants Of Protein-protein Interactionmentioning
confidence: 99%
“…Although general functions have been attributed to the mature M-MuLV Gag protein products, little is known of specific protein-protein contacts in immature or mature virions. Some genetic analyses have implicated CA as a major region of intermolecular contacts (17,18,42), and Gag-Gag binding in a yeast two-hybrid system has been attributed to the CA domain (23). The pioneering use of cross-linking agents to examine virus structure (10,32,33) demonstrated that chemical treatment of avian retroviruses produced homotypic dimers of all mature Gag proteins but did not yield any heterotypic dimers (33).…”
mentioning
confidence: 99%